2008
DOI: 10.1063/1.2995859
|View full text |Cite
|
Sign up to set email alerts
|

Toward conductive traces: Dip Pen Nanolithography® of silver nanoparticle-based inks

Abstract: Low cost, direct writing of conductive traces is highly desired for applications in nanoelectronics, photonics, circuit repair, flexible electronics, and nanoparticle-based gas detection. The unique ability of Dip Pen Nanolithography ͑DPN ® ͒ to direct write a variety of materials onto suitable surfaces with nanoscale resolution and area-specific patterning is leveraged in this work. We present a direct-write approach toward creating traces with commercially available silver nanoparticle ͑AgNP͒-based inks usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 14 publications
4
61
0
Order By: Relevance
“…10 Ink transport in DPN can be facilitated via incorporation of a high-viscosity, high boiling point liquid in the ink. 21,22 The PEG−PPG stabilized Fe(III) tosylate spin-coating solution was therefore a good candidate for developing a DPN writeable ink with the PEG−PPG exhibiting trifunctionality, namely: Fe(III) tosylate stabilization, conductivity enhancement, and ink-thickening.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Ink transport in DPN can be facilitated via incorporation of a high-viscosity, high boiling point liquid in the ink. 21,22 The PEG−PPG stabilized Fe(III) tosylate spin-coating solution was therefore a good candidate for developing a DPN writeable ink with the PEG−PPG exhibiting trifunctionality, namely: Fe(III) tosylate stabilization, conductivity enhancement, and ink-thickening.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…IWL-0009−03). The tip was bled of excess ink in a method similar to that previously reported for DPN of liquid inks 21,22 by bringing it in contact with the substrate in several (typically four to five) locations, until deposition of large ∼10 μm "bleed-spots" ceased. One further test array (25 dots of 5 s dwell time) was deposited in order to ensure the system entered a regime of reproducible submicrometer-scale patterning.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M-Type probes (material Si 3 N 4 , length 107 µm, width 22 µm, spring constant 0.5 N/m) have an ink reservoir etched into the underside of the cantilever, and this holds the ink in place to feed the tip during writing. The tip was bled of excess ink in a method similar to that previously reported for DPN of liquid inks by bringing it in contact with the substrate in several (typically 4-5) locations, until deposition of large ~10 µm 'bleed-spots' ceased [22,23,29]. All patterns were generated using the InkCAD software (v 2.7.1) provided with the Nscriptor system.…”
Section: Patterning Methodologymentioning
confidence: 99%
“…When dissolved in a reducing agent, such as ethylene glycol, the temperature of reduction is lowered significantly [31][32][33]. Ethylene glycol also has a relatively low volatility (boiling point 197 °C), an important parameter for DPN ink formulations [29]. Cho et al have shown that thin films of platinum nanoparticles could be formed by simply drop-casting H 2 PtCl 6 /EG solution onto a substrate heated to 160 °C [32].…”
Section: Ink Developmentmentioning
confidence: 99%